Actinoramide A Identified as a Potent Antimalarial from Titration-Based Screening of Marine Natural Product Extracts - Cheng, Ken Chih-Chien (2015)
Methods to identify the bioactive diversity within natural product extracts (NPEs) continue to evolve. NPEs constitute complex mixtures of chemical substances varying in structure, composition, and abundance. NPEs can therefore be challenging to evaluate efficiently with high-throughput screening approaches designed to test pure substances. Here we facilitate the rapid identification and prioritization of antimalarial NPEs using a pharmacologically driven, quantitative high-throughput-screening (qHTS) paradigm. In qHTS each NPE is tested across a concentration range from which sigmoidal response, efficacy, and apparent EC50s can be used to rank order NPEs for subsequent organism reculture, extraction, and fractionation. Using an NPE library derived from diverse marine microorganisms we observed potent antimalarial activity from two Streptomyces sp. extracts identified from thousands tested using qHTS. Seven compounds were isolated from two phylogenetically related Streptomyces species: Streptomyces ballenaensis collected from Costa Rica and Streptomyces bangulaensis collected from Papua New Guinea. Among them we identified actinoramides A and B, belonging to the unusually elaborated nonproteinogenic amino-acid-containing tetrapeptide series of natural products. In addition, we characterized a series of new compounds, including an artifact, 25-epi-actinoramide A, and actinoramides D, E, and F, which are closely related biosynthetic congeners of the previously reported metabolites.